a+1/b = x => a+1 = bx
b+1/c = x => b+1 = cx
c+1/d = x => c+1 = dx
d+1/a = x => d+1 = ax
=> a+b+c+d + 4 = x(a+b+c+d)
=>x = 1 + 4/(a+b+c+d)
2007-01-10 20:27:01
·
answer #1
·
answered by James Chan 4
·
0⤊
1⤋
a=1,b=2,c=3,d=4 and x=1
2007-01-10 21:24:21
·
answer #2
·
answered by hopest 1
·
0⤊
1⤋
(a + 1)/b = (b + 1)/c = (c + 1)/d = (d + 1)/a = x
a + 1 = bx implies a = bx - 1 (Equ.1)
b + 1 = cx implies b = cx - 1 (Equ.2)
c + 1 = dx implies c = dx - 1 (Equ.3)
d + 1 = ax implies d = ax - 1 (Equ.4)
Plug b's value from Equ.2 into Equ.1 :
a = (cx - 1)x - 1 = cx^2 - x - 1 (Equ.5)
Plug c's value from Equ.3 into Equ.5 :
a = (dx - 1)x^2 - x - 1 = dx^3 - x^2 - x - 1 (Equ.6)
Plug d's value from Equ.4 into Equ.6 :
a = (ax - 1)x^3 - x^2 - x - 1 = ax^4 - x^3 - x^2 - x - 1
Rearrange : ax^4 - a = x^3 + x^2 + x + 1
Factorise : a(x - 1)(x + 1)(x^2 + 1) = (x + 1)(x^2 + 1)
Cancel similar terms : a(x - 1) = 1, or, x = 1 + 1/a
Working backwards with the initial equation,
we find that d = a, c = d, b = c and a = b,
which means that a, b, c and d must be the
same number, so the original premise is untrue.
The value of x is 1 + 1/n, where n is a, b, c or d,
and n can be any number.
2007-01-10 23:51:56
·
answer #3
·
answered by falzoon 7
·
0⤊
0⤋
One possible solution:
a = b = c = d = 1 and x = 2.
2007-01-10 20:54:51
·
answer #4
·
answered by Brenmore 5
·
0⤊
1⤋
x = a + 1/b â bx = ab + 1
x = b + 1/c â cx = bc + 1
x = c + 1/d â dx = cd + 1
x = d + 1/a â ax = da + 1
(a + b + c + d)x = ab + bc + cd + da + 4
x = (ab + bc + cd + da + 4)/(a + b + c + d)
2007-01-10 20:43:25
·
answer #5
·
answered by Northstar 7
·
1⤊
0⤋
a+1=bx
b+1=cx
d+1=ax
c+1=dx
=> bx-a=cx-b=ax-d=dx-c=1
=> bx+b=cx+c=dx+d=ax+a=1
=> b(x+1)=c(x+1)=d(x+1)=a(x+1)=1
=> a=b=c=d=1/(x+1)
So in this way a,b,c,d shouldn't be diffrend numbers ! :-)
2007-01-10 20:50:42
·
answer #6
·
answered by Arash J 2
·
0⤊
0⤋